Wage inequality in Spain: A regional perspective - Ismael Ahamdanech; Carmelo García-Pérez; Hipolito Simon (European Regional Science Association (ERSA), 2011)
The research examines wage inequality in the Spanish labour market from a regional perspective, drawing on stochastic dominance techniques. The field of study is of particular interest because wage determination in Spain incorporates an important territorial component, facilitated by certain specific institutional elements, given that Spain is one of the few developed countries in which collective bargaining is mainly developed through industry-wide agreements on an infra-national scale applied exclusively to provinces or regions. The main empirical findings are that wage inequality exhibits a significant regional heterogeneity and that both regional differences in workforce heterogeneity and the mix of jobs and workplaces and differences in their wage returns are influential factors in the explanation of regional heterogeneity in the levels of wage inequality. Consequently, the infrequent regional dimension of collective bargaining on an industry level implies the presence in Spain of wage determination mechanisms that are differentiated by region, which give rise to the existence of significant differences in regional wage structures.
Keywords: 330